Prevalence and oncologic outcomes of BRCA 1/2 mutations in unselected triple-negative breast cancer patients in Korea - Ryu, Jai Min; Choi, Hee Jun; Kim, Isaac; Nam, Seok Jin; Kim, Seok Won; Yu, Jonghan; Lee, Se Kyung; Choi, Doo Ho; Park, Yeon Hee; Kim, Jong-Won; Seo, Jeong-sun; Park, Jung-Hoon; et al. (Breast cancer research and treatment, 2019)
Purpose Triple-negative breast cancer (TNBC) accounts for 10–20% of all diagnosed BCs and it is enriched in BRCA1 mutation. Guidelines for Western countries suggest that BRCA 1 / 2 genetic testing should be done for patients with TNBC diagnosed less than 60 years, but there is lack of evidence supporting genetic testing in Asian populations. We determined the prevalence of germline BRCA 1 / 2 mutations among unselected Korean patients with TNBC and analyzed oncologic outcomes. Methods From among 1628 women with TNBC who underwent surgery at Samsung Medical Center (SMC) between Jul 2008 and Jan 2016, 999 samples were available in the SMC biobank for testing germline BRCA 1 / 2 mutations using next-generation DNA sequencing. Results Overall, 131 Korean patients (13.1%) had BRCA 1 / 2 mutations: 97 (9.7%) were in BRCA 1 , and 35 (3.5%) were in BRCA 2 . One patient had both BRCA 1 and BRCA 2 mutations. Overall, 68 distinct pathologic or likely pathogenic variants (43 BRCA1 and 25 BRCA2 ) were found. Among those diagnosed at ≤ 60 years, the prevalence of BRCA 1 / 2 mutation was 14.5%. The mean age of diagnosis of BRCA1 / 2 mutation carriers was significantly younger than that of non-carriers (45.6 vs. 50.1 years, p < 0.0001). The median follow-up duration was 53.6 months. There were no significant differences in disease-free survival, overall survival, or breast cancer-specific survival ( p = 0.799, 0.092, and 0.124, respectively) between BRCA 1 / 2 carriers and non-carriers, although BRCA 1 / 2 carriers showed significantly worse contralateral breast cancer-free survival ( p < 0.0001) than non-carriers. Conclusion In unselected TNBC patients, we found BRCA 1 / 2 mutations in 13.1% of overall patients and 14.5% of patients ≤ 60 years. We suggest that Korean women with TNBC diagnosed at ≤ 60 years should be tested for BRCA1 / 2 mutation.